Research and study paths at the university: a praxeological model of reference related to costs calculation Parcours de recherche et d’études à l’université: un modèle praxéologique de référence lié au calcul des coûts - Salgado, Diana Patricia; Otero, María Rita; Parra, Verónica (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2020)
Abstract This work fits within a wider research whose general objective is teaching mathematics to non-mathematicians at the university, taking central assumptions of the Anthropological Theory of Didactics. This work proposes a praxeological model of reference related to a micro-entrepreneurship costs calculation. The generative question How to calculate micro-entrepreneurship costs? links mathematical and economic praxeologies. This model allows to go through a part of the study programme of a university calculus course. Keywords: Anthropological theory of the didactic; Course of study and research; Praxeological Reference Model. Résumé Ce travail fait partie d’une recherche plus large dont l’objectif général est l’enseignement des mathématiques pour non-mathématiciens à l’université dans le cadre de la Théorie Anthropologique du Didactique. On propose un modèle praxéologique de référence sur le calcul de coûts d’une micro-entreprise. La question génératrice est Comment calculer les coûts dans une micro-entreprise? Elle associe plusieurs organisations mathématiques et économiques. Ce modèle permet de couvrir une partie du programme d’études d’un cours de Calcul du niveau universitaire. Mots-clés : Théorie anthropologique de la didactique, Parcours d’étude et de recherche, Modèle de référence praxéologique.